IMPACTS OF DELAYED FIELD CURING ON RICE SEED QUALITY IN A TROPICAL ENVIRONMENT. (5th April 2018) - BAM, R. K.; SERSHEN,; VARGHESE, B.; DZOMEKU, B. M.; APPIAH-KUBI, Z.; PAMMENTER, N. W.
SUMMARY: Three upland rice species, viz. Oryza sativa, Oryza glaberrima and an O. sativa × O. glaberrima interspecific hybrid, were grown in Ghana, harvested, and field cured under open (wet) and within ventilated but rainproof containers (dry) conditions for 5 weeks. Seeds from both environments were assessed weekly for physical, physiological and pathological quality. The relationships between air temperature and relative humidity, and seed moisture content (MC) and water activity differed between curing environments but within curing environments, relationships between seed MC and water activity were comparable among species. Prolonged field curing resulted in structural damage evidenced by the formation of multiple cracks in the endosperm; these were more frequent in wet cured seeds. Diverse fungal species were isolated from wet (22 species) and dry (23 species) cured seeds with a number of soil-borne species in the wet environment. Curing environment did not influence levels of fungal infection in O. glaberrima seeds but dry curing was associated with higher levels of fungal infection in O. sativa and O. sativa × O. glaberrima . Seed germinability in all the three species was higher in the dry cured seeds although vigour was relatively lower than wet cured seeds. Field curing the seeds of these three species within a dry environment could potentially improve subsequent seed viability, aid in moisture management and minimize structural damage to the endosperm; however, research on how fungal infection could be curbed under such conditions is needed.